Dietary habits and physical activity patterns in relation to nutritional status among school-aged children in Pakistan: A cross-sectional study - Saleem Qureshi; Musarrat Iqbal; Azra Rafiq; Hamna Ahmed; Tooba Malik; Muhammad Nasir Kalam; Muhammad Abdullah; Qirtas Tauheed; Muhammad Daoud Butt (AIMS Press, 2023)
Background: Childhood malnutrition remains a significant public health problem impacting the physical and mental growth if school aged children, particularly in limited-resource countries. Objective: The study objective was to assess levels of physical activity, patterns of screen time (S.T.), the relationship between physical activity and screen time patterns, and how these factors affect growth status (adjusting for socioeconomic status). Methodology: A cross-sectional study included 3,834 children between 6-14 years attending pre-selected schools. Teachers, students, and parents were invited to fill out a standardized questionnaire, and Body Mass Index (BMI) was calculated using Center for disease control (CDC) centile charts. A Chi-square was performed to see the possible association between any height and weight abnormalities and all possible risk factors. Multivariate logistic regression was applied to see the effect of variables significantly associated with univariate analysis. Results: Approximately 2,447 (63.8%) children were between 11-14 years old and 1,387 (36.2%) were between 4-10 years old. The mean height was 143.71 ± 16.51 centimetres, the mean weight was 36.5 ± 12.9 kilogram, and the mean BMI was 17.16 ± 3.52. Multivariate logistic regression status and junk food combined affected stunting socioeconomic status was significantly associated with being underweight p = 0.001. Conclusion: Childhood obesity and stunting remain significant problems in Pakistani school-going children. These are significantly associated with poverty, a lack of physical activity opportunities, and available food quality.